Identification of structural displacements utilizing concurrent robotic total station and GNSS measurements - Pehlivan, Hüseyin (Techno-Press, 2022)
Monitoring large structures is a significant issue involving public health on which new studies are constantly carried out. Although the Global Navigation Satellite System (GNSS) is the most preferable method for measuring structural displacements, total stations, one of the classical geodetic instruments, are the first devices that come to mind in cases that require complementary usage and auxiliary measurement methods. In this study, the relative displacements of the structural movements of a tower were determined using robotic total stations (RTS) and GNSS. Two GNSS receivers and two RTS observations were carried out simultaneously for 10 hours under normal weather conditions. The spectral analysis of the GNSS data was performed using fast Fourier transform (FFT), and while the dominant modal frequencies were determined, the total station data were balanced with the least-squares technique, and the position and position errors were calculated for each measurement epoch. It has been observed that low-frequency structural movements can be determined by both methods. This result shows that total station measurements are a helpful alternative method for monitoring large structures in situations where measurements are not possible due to the basic handicaps of GNSS or where it is necessary to determine displacements with short observations.
Keywords: FFT; GNSS; robotic total station; structural displacement; the least-squares method